Crowd logistics: Understanding auction-based pricing and couriers' strategies in crowdsourcing package delivery. Issue 2 (4th March 2022) - Rechavi, Amit; Toch, Eran
Abstract: The growth of electronic commerce generates significant demand for the delivery of personal goods. Crowdsourcing applications have the potential to create more flexible alternatives to existing package-delivery services. However, the success of these applications is strongly related to the strategies of the crowd couriers, which are not well-understood in the current literature. In this paper, we analyzed data from a real-world crowdsourcing application that uses an auction-based mobile app to deliver small packages in urban, suburban, and intra-metropolitan areas. Our analysis reveals the spatial strategies of crowdsourced couriers, which are correlated with delivery pricing and the courier's experience. The couriers with strong relationships with specific customers create ongoing trust relations, which makes deliveries over medium distance routes financially reasonable for those couriers. We discuss how our findings can help to maximize package-delivery markets and crowdsourcing markets in general by supporting the couriers' strategies.